Spontaneous anal expulsion of an osteosarcoma in a cat - Rissi, Daniel R. (Brazilian Journal of Veterinary Pathology, 2024)
A 6-year-old spayed female domestic short hair cat was evaluated because of a 1-month history of straining to defecate and partial rectal prolapse, with expulsion of a 1 cm in diameter, white-to-red, firm-to-hard, homogenous nodule from the anus. The nodule was collected by the submitting veterinarian and submitted for histologic examination. Histologic features were consistent with an osteosarcoma. The cat was euthanized, and no autopsy was performed. Although the origin of the osteosarcoma could not be determined, the clinical history was suggestive of a lower gastrointestinal tract osteosarcoma that detached from its primary site and exited through the anus, similar to what is rarely reported for intestinal polyps and lipomas in human medicine. No reports of such event were found in veterinary medicine.